Dendritic molecular assemblies for singlet oxygen generation: meso-tetraphenylporphyrin-based biphotonic sensitizers with remarkable luminescence. (27th July 2015) - Yao, Dandan; Hugues, Vincent; Blanchard-Desce, Mireille; Mongin, Olivier; Paul-Roth, Christine O.; Paul, Frédéric
Abstract : Thanks to its 2-ethynylflorenyl-containing arms, dendrimer1 sensitizes molecular oxygen in 70% yield and exhibits a fluorescence yield of 20%. Abstract : Four new TPP-based chromophores (1–4 ) peripherally functionalized with dendrons containing 2-fluorenyl groups were studied for their potential to serve in photodynamic therapy. Their linear and nonlinear optical properties were investigated. With significant TPA cross-sections at 790 nm, good singlet oxygen generation capabilities and relatively large intrinsic fluorescence, sensitizers such as1 might become particularly appealing for theranostics.